Mapping Waqf Research: Bibliometric Analysis (ZISWAF: Jurnal Zakat dan Wakaf, 2022)
The purpose of this study is to examine Indonesia's waqf development pattern. Waqf-related research includes, among other things, the study of waqf law, productive waqf schemes, empowering waqf for poverty, stock waqf, and waqf connected to sukuk. The most popular articles are frequently those that discuss how waqf can reduce poverty and promote economic empowerment. Studies on the professionalism of waqf institutions in Indonesia are relatively few. A review of the literature on the management of waqf institutions in favor of professionalism was done by the researchers in light of this. This study is a quantitative investigation that makes use of bibliometric analysis. A quantitative strategy for examining bibliographic information in papers and journals is called bibliometrics. In this study, a waqf journal that Google Scholar has indexed served as the population. Publish or Perish 8 was used to select the samples for this study, which were publications with the keywords "management of waqf institutions," "waqf institutions," and "professionalism of Nazhir" in Indonesia. The information demonstrated an increase in the number of publications since the average year. According to Google Scholars, there were 82, 89, 110, 141, 147, 143, and 195 more publications about endowment per year from 2015 to 2021. The research's key themes were the effects of waqf on the role of nazhirs, effective waqf management, and nazhir certification. Future research plans are anticipated to concentrate on the professional behavior of waqf institutions and how to best foster professionalism through waqf institutions. In Indonesian waqf institutions, there is a level of professionalism known as nazhir certification. This study is intended to advance waqf research both domestically and internationally so that waqf research can expand with new topics and become more diverse.